2022
DOI: 10.1128/mcb.00081-22
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Role of Secretory Cytosolic Tryparedoxin Peroxidase in Delaying Apoptosis of Leishmania-Infected Macrophages

Abstract: The cytosolic tryparedoxin peroxidase (cTXNPx) of Leishmania donovani is a defensive enzyme. Apart from the nonsecretory form, the cTXNPx is released in the spent media of Leishmania cultures and also in the host cell cytosol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…Exoproteome analysis of L. donovani revealed that the parasite secretes a repertoire of secretory molecules including, molecules for immunomodulation and evasion [glycoprotein 63 (gp63), elongation factor 1α (EF1α), oligopeptidase, proteophosphoglycan (PPG)], increased pathogenicity [chitinase, casein kinase, KMP-11, cysteine peptidase and metalloproteases], and parasite protection [tryparedoxin peroxidase (cTXNPx)], which influence the pathophysiology of the disease by induction of inflammatory cytokines, particularly IL-17a [ 139 , 140 , 141 , 142 , 143 , 144 , 145 , 146 , 147 , 148 , 149 , 150 , 151 , 152 , 153 , 154 , 155 ] and/or implicated in drug-resistance in parasites [ 155 ]. Exosomes secreted by drug-resistant parasite form a nucleosome complex with human histone in host chromatin during the progression of the disease [ 156 ].…”
Section: Ltps and Their Biological Implicationsmentioning
confidence: 99%
“…Exoproteome analysis of L. donovani revealed that the parasite secretes a repertoire of secretory molecules including, molecules for immunomodulation and evasion [glycoprotein 63 (gp63), elongation factor 1α (EF1α), oligopeptidase, proteophosphoglycan (PPG)], increased pathogenicity [chitinase, casein kinase, KMP-11, cysteine peptidase and metalloproteases], and parasite protection [tryparedoxin peroxidase (cTXNPx)], which influence the pathophysiology of the disease by induction of inflammatory cytokines, particularly IL-17a [ 139 , 140 , 141 , 142 , 143 , 144 , 145 , 146 , 147 , 148 , 149 , 150 , 151 , 152 , 153 , 154 , 155 ] and/or implicated in drug-resistance in parasites [ 155 ]. Exosomes secreted by drug-resistant parasite form a nucleosome complex with human histone in host chromatin during the progression of the disease [ 156 ].…”
Section: Ltps and Their Biological Implicationsmentioning
confidence: 99%